Toxicología ambiental en minería: herramientas para la evaluación del impacto - Zegarra Macchiavello, Darío (2003)
The growing interest in the effects that mining causes on the environment has given rise to new forms of prevention and control in this industry. The start-up of a mining operation can be understood as an alteration of an ecosystem in equilibrium it is already part of a system seeking equilibrium. But how much has the balance been broken and for how long? How to quantify the effect on biota inventories of the affected area? How to consider the bioaccumulation of xenobiotics in the habitat? How to include so many variables their relationships and their temporal evolution? The analysis through the time of these alterations or redefinitions of the variables present in the environment must be considered for a study of the impact on the environment. This paper presents criteria and tools for the analysis of the effects that a mining or industrial operation causes in its surrounding environment. The Probabilistic Risk Assessment (or Monte Carlo Simulation) and the Modelling of Dynamic Systems are analysed tools whose common base is the simulation of models as an approach for the development of summary representations of reality. In order to show the practicality relevance and applicability of these approaches a case study of each of them is reviewed.